Fracture Toughness Evaluation of Hybrid and Nano-hybrid Resin Composites after Ageing under Acidic Environment - Ferooz M; Basri F; Negahdari K; Bagheri R (Shiraz University of Medical Sciences, 2015)
Statement of Problem: Tooth-coloured restorative materials are brittle with the major shortcomings of sensitivity to flaws and defects. Although various mechanical properties of resin composites have been studied, no fracture toughness test data for nano-hybrid composites under acidic condition for a long period of time has been published. Objectives: To compare the fracture toughness (KIc) of two types of resin composites under tensile loading and to assess the effect of distilled water and lactic acid on the resistance of the restoratives to fracture after three months of immersion. Materials and Methods: Four resin composites were used: three nanohybrids [EsteliteSigma Quick (Kuraray), Luna (SDI), Paradigm (3M/ESPE)] and one hybrid, Rok (SDI). The specimens were prepared using a custom-made polytetrafluorethylene split mould, stored in distilled water (pH 6.8) or 0.01mol/L lactic acid (pH 4) and conditioned at 37°C for 24 hours, 1 or 3 months. They were loaded under tensile stress using a universal testing machine; the maximum load (N) to the specimen failure was recorded and the fracture toughness (KIc) was calculated. Data were analysed by ANOVA and Tukey's test using SPSS, version 18. Results: The results of two-way ANOVA did not show a significant combined effect of material, time, and storage medium on fracture toughness (p= 0.056). However, there was a strong interaction between materials and time (p=0.001) when the storage medium were ignored. After 24 h of immersion in distilled water, Paradigm revealed the highest KIc values followed by Rok, Luna and Estelite. Immersion in either distilled water or lactic acid significantly decreased the fracture toughness of almost all materials as time interval increased. Conclusions: Paradigm showed the highest fracture toughness followed by Rok, Luna and Estelite respectively. As time increased, KIc significantly decreased for almost all resin composites except for Luna which showed a slight decrease after one month of immersion in distilled water.